Factors associated with quality of life in caregivers of patients with multiple myeloma: QoL in caregivers of multiple myeloma patients - Doğan, Esma Evrim; Demirel, Naciye (Journal of Surgery and Medicine, 2023)
Background/Aim: Advances in the therapeutic treatment of multiple myeloma have continuously led to better prognoses. However, longer lives for patients include complications due to both potential comorbidities and the possible severe side effects of specific treatments. These issues make caring for such patients exhausting. In this study, we investigated the most important factors that negatively affect the quality of life (QoL) of non-professional caregivers of patients with multiple myeloma (MM). Methods: This study was a cross-sectional study conducted between March 2023 and August 2023. The caregivers of 144 patients with MM were assessed for inclusion/exclusion. The demographics of caregivers, their familial relation to the patient, and their socioeconomic status (education, both marital and financial status, and occupations) were recorded. Additionally, data from MM patients were retrieved: (1) clinical and demographic data, (2) light and heavy chain types, (3) disease stage, (4) lytic lesions, and (5) treatment(s). The Caregiver Quality of Life Index-Cancer (CQOLC) questionnaire contains four sub-scores and a total score and was administered to all caregivers who volunteered to participate. Results: A total of 73 patients and their caregivers were included in the study. For patients, their mean age was 65.7 (11.4) years, 52% were female, and the mean value of the disease duration was 30.5 (16.0–66.5) months. For caregivers, their mean age was 47.2 (12.8) years, and 63% were females. Multivariable linear regression revealed that higher (>40 years) caregiver age was independently associated with a higher CQOLC Burden and Positive adaptation score. Being a female caregiver was independently associated with a higher CQOLC Disruptiveness score. Having university-level or higher education status was independently associated with a lower CQOLC Financial Concerns score. In terms of the overall score, we found that higher (>40 years) caregiver age and the gender of the caregiver (female) appear to be factors that are independently associated with higher CQOLC total scores, whereas being a second-degree relative to the patient independently lowered the total score. Conclusion: Among caregivers of MM patients, those who were older, female, and/or the first-degree relative of the patient (versus second-degree) with having lower education (versus university or higher) resulted in an improved caregiver QoL. The gender bias among caregivers is also a novel finding.